THE GENER OF POETRY IN XVII CENTURY - Shamurodova S.X (Ta'lim innovatsiyasi va integratsiyasi, 2023)
The purpose of writing this article is give novices directly facts and information according one of the eminent gener is that poetry.Any century's poetry can be asked whether it owes its identity primarily to the practice of its most innovative and prominent poets, or whether it owes its character to "forces"—nonliterary phenomena to which the poets respond, more or less sensitively. The cases of William Shakespeare and John Milton, the twin titans of seventeenth-century England, demonstrate that great poets do not inevitably influence the literature of their century. Ben Jonson's assessment of Shakespeare holds true for both: They are "forever, not just of a certain age!" But two poets who seem to have left their marks on a lot of their own and later generations' poetry are John Donne and John Dryden.Literary scholars have focused much of their attention on innovations that began with Donne and Jonson in the seventeenth century, but the Spenserian legacy should not be overlooked. Its master, the multifaceted poet Edmund Spenser, left behind a rich and varied tradition. The Spenserian pastoral adaptations of Michael Drayton were carried into the early 21st century and into the approaching fourth decade. The greatest English poet since Shakespeare discovered the ideal template for his own epic in The Faerie Queene. Some poets emulated Spenser's idealism, while others focused on his demanding stanza, his achievement in romantic tale, and his sensual, even sensual music. There was no writer of the seventeenth century quite like Spenser, but his genius continued to shine throughout the century and even beyond.